3 D Network‐Structured Crumpled Graphene/Carbon Nanotube/Polyaniline Composites for Supercapacitors. Issue 10 (26th April 2017) - Jo, Eun H.; Jang, Hee D.; Chang, Hankwon; Kim, Sun K.; Choi, Ji‐Hyuk; Lee, Chong M.
Abstract: Crumpled graphene (CGR) is considered a promising supercapacitor material to achieve high power and energy density because it could overcome the disadvantages of 2 D GR sheets such as aggregation during the electrode fabrication process, reduction of the available surface area, and limitation of the electron and ion transport. Even though CGR shows good results, carbon materials are limited in terms of their capacitance performance. Here, we report highly enhanced supercapacitor materials by fabricating a 3 D composite containing CGR, carbon nanotubes (CNTs), and polyaniline (PANI). The CNTs increased the basal spacing and bridged the defects for electron transfer between the GR sheets in CGR. PANI can enhance the rate of conduction of electrons and offer high pseudocapacitance originating from its redox reactions. The synergistic effect of the CNTs and PANI may also result in a higher electrochemical capacitance and better stability than each individual component as electrode materials for supercapacitors in a two‐electrode system. More importantly, the performance of the supercapacitors can be further enhanced by employing 2 D GR as the binder for the composite electrodes, resulting in specific capacitance of 456 F g −1, rate capability of 89 %, and cyclic stability of 97 % after 1000 cycles. Abstract : Super‐crumpled : Highly enhanced supercapacitor materials by fabricating a 3 D composite containing crumpled graphene, carbon nanotubes, and polyaniline are reported. The performance of the supercapacitors is further enhanced by employing 2 D graphene as the binder for the composite electrodes.